Thermal analysis in Ti-6Al-4V drilling. Issue 1 (2017) - Lazoglu, Ismail; Poulachon, Gérard; Ramirez, Christophe; Akmal, Mohammad; Marcon, Bertrand; Rossi, Frédéric; Outeiro, José C.; Krebs, Michaël
Abstract: Ti-6Al-4V is commonly used especially in aerospace and biomedical industries. This alloy is known as a difficult-to-cut material. Due to its poor thermal properties, the heat generated during machining processes traps near material deformation zones. This causes detrimental high temperatures for the cutting tools. This article combines the analytical and FEM modeling techniques to estimate the temperature evolution of carbide tools in Ti-6Al-4V drilling. In this article, a novel thermocouple based temperature measurement setup is also introduced. Moreover, the simulated and measured temperatures under various cutting conditions for the drilling of Ti-6Al-4V are presented for the validation.